TTF‐1 expression in breast carcinoma: an unusual but real phenomenon. Issue 4 (25th November 2013) - Ni, Yun‐Bi; Tsang, Julia Y S; Shao, Mu‐Min; Chan, Siu‐Ki; Tong, Joanna; To, Ka‐Fai; Tse, Gary M
<x xml:space="preserve">Abstract</x> Aims To evaluate thyroid transcription factor‐1 (TTF‐1) expression in a large cohort of invasive breast carcinomas (IBCs) using two commercially available monoclonal antibody clones (8G7G3/1 and SPT24). Methods and results Nuclear and cytoplasmic TTF‐1 expression was evaluated in 1132 primary IBCs and 208 primary pulmonary carcinomas using tissue microarray (TMA) sections. TTF‐1 nuclear expression was detected in one of 1132 (0.09%) IBCs by 8G7G3/1. In pulmonary carcinoma, TTF‐1 expression was detected in 149 (71.6%) and 147 (70.6%) cases by 8G7G3/1 and SPT24, respectively, with no significant difference being seen between the two clones (P = 0.839), and there was good consistency between these two antibodies in differentiating breast and pulmonary carcinomas (kappa value 0.905; P < 0.001). Both clones showed high specificity but relatively low sensitivity. Cytoplasmic TTF‐1 expression was detected in 44 IBCs by 8G7G3/1, and this particular expression pattern was an independent adverse prognostic factor. Conclusions Both TTF‐1 antibodies (clones 8G7G3/1 and SPT24) were useful in differentiating breast from pulmonary carcinomas. Nuclear expression of TTF‐1 was detected in IBCs by 8G7G3/1, but not by SPT24. Cytoplasmic expression of 8G7G3/1 was seen in IBC for the first time, and was an independent unfavourable prognostic factor.